2016
DOI: 10.1177/0269215516629722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training with a passive hand orthosis and games at home in chronic stroke: a pilot randomised controlled trial

Abstract: Both interventions were accepted. An additional benefit of technology-supported arm and hand training over conventional arm and hand exercises at home was not demonstrated. Training duration in itself is a major contributor to arm and hand function improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(150 citation statements)
references
References 29 publications
2
145
0
3
Order By: Relevance
“…A home-training study with SPO reported gains in the FM similar in magnitude to what we observed [46], however a second controlled study found no differences between this experimental home treatment and a control group that received a standard home exercise regime [47]. Similar to our results, these 2 studies with SPO also observed a large variance across subjects in the amount of therapy performed and significant dosage effects.…”
Section: Discussionsupporting
confidence: 87%
“…A home-training study with SPO reported gains in the FM similar in magnitude to what we observed [46], however a second controlled study found no differences between this experimental home treatment and a control group that received a standard home exercise regime [47]. Similar to our results, these 2 studies with SPO also observed a large variance across subjects in the amount of therapy performed and significant dosage effects.…”
Section: Discussionsupporting
confidence: 87%
“…6), indicates that participants also regarded the HiM system as an interesting, useful and motivational system to use, aimed at improving their hand function during daily life. The studies from Nijenhuis et al (32) and Radder et al (31) showed lower overall IMI scores for stroke patients and elderly people using robotic hand devices for training purposes or assistance in daily life. Interestingly, the studies of Nijenhuis et al (24,32) showed that stroke patients were able to use a robotic training device, that received lower SUS and IMI scores, for the upper limb independently at home for at least 105 min a week.…”
Section: User Acceptancementioning
confidence: 96%
“…The studies from Nijenhuis et al (32) and Radder et al (31) showed lower overall IMI scores for stroke patients and elderly people using robotic hand devices for training purposes or assistance in daily life. Interestingly, the studies of Nijenhuis et al (24,32) showed that stroke patients were able to use a robotic training device, that received lower SUS and IMI scores, for the upper limb independently at home for at least 105 min a week. This may suggest that stroke patients might be able and motivated to integrate the HiM system into use in daily life.…”
Section: User Acceptancementioning
confidence: 96%
“…The study of Rogers et al 2007 (38) showed that older adults with hand osteoarthritis can improve dynamic and static handgrip strength and reduce pain after strength training. Muscle function and fitness of patients with rheumatoid arthritis can also improve after 30-60 minutes strength exercises or aerobic exercises (3x/week) (39). However, patients with osteoarthritis and rheumatoid arthritis are advised to perform in particular low-impact activities, such as swimming, walking, cycling, to decrease the chance on joint inflammation (40).…”
Section: Hand Rehabilitationmentioning
confidence: 99%